Integrasi Nilai Agama Dan Budaya Dalam Pendidikan Islam Multikultural - Syahdania, Syafa Dwi Kalam; Suryaningtyas, Pramesti Retno (JURNAL MANAJEMEN PENDIDIKAN, 2026)
INTEGRATION OF RELIGIOUS AND CULTURAL VALUES IN MULTICULTURAL ISLAMIC EDUCATION Abstract This study aims to understand how religious and cultural values are integrated into multicultural Islamic education in Indonesia. In a diverse society, Islamic education plays a vital role in shaping students to become faithful, tolerant, and morally upright individuals. This research employs a library research method by analyzing various sources such as books, journals, and policy documents that discuss the integration of religious and cultural values. The findings show that Islamic values such as justice, compassion, brotherhood, and tolerance align with local cultural values like gotong royong (mutual cooperation), sopan santun (politeness), and tepo seliro (empathy). By integrating these values, Islamic education not only strengthens religious identity but also fosters stronger social and national awareness. The implementation of multicultural Islamic education can be carried out through a value-based curriculum, contextual approaches, the teacher’s role as a cultural mediator, and extracurricular activities that combine Islamic teachings with local traditions. Challenges include rigid religious interpretations, limited teacher competence in multicultural teaching, and the influence of globalization that weakens cultural values. This study suggests strengthening religious moderation, providing teacher training based on local wisdom, and developing a curriculum suited to local contexts. Thus, Islamic education is expected to form a society that is faithful, knowledgeable, cultured, and harmonious within the framework of rahmatan lil ‘alamin.